Andean roots and tubers: Ahipa, arracacha, maca and yacon - Hermann, M.; Heller, J.; Leibniz Institute of Plant Genetics and Crop Plant Research; International Plant Genetic Resources Institute (1997)
At least 25 species of root and tuber crops from 16 genera and 15 families are native to South America. Apart from the 7 species of potato (Solanum spp.), there are nine lesser known species native to the Andes that are grown for their edible underground organs and are traditionally, but not exclusively, cultivated by indigenous people who use them for subsistence or as cash crops. This book is the first of two volumes to deal in depth with the biology and genetic resources of these Andean root and tuber crops, and, following an introduction, is divided into 4 multiauthor sections: (1) ahipa (Pachyrhizus ahipa) by M. Sorensen, W. J. Gruneberg and B. Orting; (2) arracacha (Arracacia xanthorrhiza) by M. Hermann; (3) maca (Lepidium meyenii) by C. F. Quiros and R. Aliaga Cardenas; and yacon (Smallanthus sonchifolius) by A. Grau and J. Rea. Each section follows the standard format for the series and reviews aspects of their taxonomy, botany, origin, ecology, properties, uses, conservation, evaluation of diversity and breeding. In addition, full accounts are given of crop production areas, agronomy, limitations, prospects and research needs. A single appendix lists research workers by country. (Abstract © CAB ABSTRACTS, CAB International)